2009
DOI: 10.1242/dev.037028
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of preprocambial cell state acquisition by auxin signaling inArabidopsisleaves

Abstract: The principles underlying the formation of veins in the leaf have long intrigued developmental biologists. In Arabidopsis leaves, files of anatomically inconspicuous subepidermal cells that will elongate into vein-forming procambial cells selectively activate ATHB8 gene expression. The biological role of ATHB8 in vein formation and the molecular events that culminate in acquisition of the ATHB8 preprocambial cell state are unknown, but intertwined pathways of auxin transport and signal transduction have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
330
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 264 publications
(351 citation statements)
references
References 86 publications
20
330
0
1
Order By: Relevance
“…Loss of A2 alone [pS15-2E (DA2)::LUC] drastically reduced auxin induction of LUC activity, demonstrating that A2 is acting as an essential AuxRE in the SAUR15 promoter. Recently, another element with the same sequence as A2 (CA-GACA) was found to act as a bona fide AuxRE in the unrelated ATHB8 promoter (Donner et al, 2009). Consistent with this finding, we observed that loss of A2 alone [pS15-2E(DA2)::LUC] drastically reduced auxin induction of the reporter, demonstrating that A2 (CAGACA) but not A5 (GAGACA) is the AuxRE for SAUR15.…”
Section: Auxin and Brassinosteroid Induction Of Saur15 Requires Two Csupporting
confidence: 87%
See 1 more Smart Citation
“…Loss of A2 alone [pS15-2E (DA2)::LUC] drastically reduced auxin induction of LUC activity, demonstrating that A2 is acting as an essential AuxRE in the SAUR15 promoter. Recently, another element with the same sequence as A2 (CA-GACA) was found to act as a bona fide AuxRE in the unrelated ATHB8 promoter (Donner et al, 2009). Consistent with this finding, we observed that loss of A2 alone [pS15-2E(DA2)::LUC] drastically reduced auxin induction of the reporter, demonstrating that A2 (CAGACA) but not A5 (GAGACA) is the AuxRE for SAUR15.…”
Section: Auxin and Brassinosteroid Induction Of Saur15 Requires Two Csupporting
confidence: 87%
“…Previous studies suggested that MP/ARF5 regulates SAUR15 expression (Schlereth et al, 2010) and can bind to A2-like elements (Donner et al, 2009). We performed ChIP assays on pMP::MP:GFP seedlings using primers flanking the critical minimal region where we observed BES1 binding.…”
Section: Treatment With Either Auxin or Brassinosteroids Canmentioning
confidence: 99%
“…The pATHB8-GUS marker for the provascular cell state revealed a defective venation patterning in the elo mutants, with disconnected primary loops and reduced secondary and tertiary veins, which is typical for an altered auxin distribution (Fig. 3 D and E) (22).…”
Section: Gfp-elo3 Protein Localization In Euchromatic Regions In Intementioning
confidence: 90%
“…On the basis of the elo phenotypes and the transcriptome, we identified a number of genes with reduced expression levels (Table S3) as putative targets of Elongator, i.e., the SHY2/IAA3 and BDL/ IAA12 repressors, the ATHB8 auxin response gene (22), the LAX2 influx carrier, the PIN4 efflux carrier, and the AP2/ERF ethylene response gene. The down-regulation of these genes in the elo mutants was verified with quantitative (q)PCR (Fig.…”
Section: Hormonal Misregulation Might Contribute To the Pleiotropicmentioning
confidence: 99%
“…We aimed to identify novel MP target genes involved in the earliest events of embryonic root meristem initiation in the globular-stage embryo. As most MP target genes are expected to be activated by MP (17,(26)(27)(28)(29), we focused our analysis on the 145 down-regulated genes in the globular-stage embryo (SI Appendix, Table S1). Among these genes, ∼25% are transcription factors (36 of 145 genes) and 27 were also downregulated in heart-stage embryos (Fig.…”
Section: Mpdependent Stringent Targetsmentioning
confidence: 99%